Neokorie für Nikaia unter Trajan - Sponsel-Schaffner, Christina; Dreyer, Boris; Meriç, Aygün Ekin (Gephyra. Zeitschrift für Geschichte und Kultur der Antike auf dem Gebiet der heutigen Türkei, 2024)
This article presents an inscription found in 2023 in the theatre of Nicaea on a gallery keystone with partially preserved remnants of the painting of the letters, naming a hitherto unknown governor of the province of Bithynia and Pontus-Marcus Iulius Alpinus Classicianus-and proving the status of Nicaea as a neocoria for the reign of Emperor Trajan. Interestingly, the erasure of individual letters was carefully carried out in 192 AD.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Bithynia et Pontus; governor; Marcus Iulius Alpinus Classicianus; neocoria; Nicaea; Trajan